The Backyard Naturalist - Tufts, Craig; National Wildlife Federation, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
Many wildlife enthusiasts are aware of the need for planting certain flowers, shrubs, and trees to attract animals. Some arrange their yards to provide for food, water, cover, and areas for animals to bear and raise their young. These include city dwellers who create mini-refuges in tiny urban plots and suburbanites who design elaborate landscapes. This book is made up of selections from the nationally distributed column "The Backyard Naturalist." There are six chapters: (1) "Making a Place for Wildlife," which is a call for less lawn to provide for more interesting gardening and recreational opportunity space for family; (2) "Feeding Birds," which outlines preparation needs, types of bird food, and the kinds of birds attracted by certain foods; (3) "Who's Who among Backyard Birds," which names and describes some birds and their characteristics; (4) "Making Other Visitors Welcome," which includes butterflies, isopods, and owls; (5) "It's a Jungle Out There," in which good bugs and bad bugs, problem animals and pests, and dealing with trash are the main thrust; and (6) "Wooing Wildlife with Water, Flowers, and Shelter," in which the basic needs are emphasized. Illustrations and an index are provided. (RT)
Availability: National Wildlife Federation, 1400 16th Street, NW, Washington, DC 20036 ($6.95, Item No. 19737).
ERIC Note: Drawings may not reproduce well.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Animals; Biological Sciences; Botany; Conservation (Environment); Ecology; Environmental Education; Physical Environment; Wildlife; Zoology; Books